La construcción de hegemonía durante los años ochenta en Argentina: La alfabetización como estrategia del Estado para educar el consenso - Wanschelbaum, Cinthia (2014)
In this paper we present some ideas and concepts about the relationship between hegemony and education through the study of a particular historical moment in the history of Argentina, Raúl Alfonsín´s goverment (1983-1989), and the analysis of educational policy implemented by the government: the National Literacy Project. We understand that the Project consisted in a pedagogical strategy of hegemony to educate the consensus. The National Literacy Project was oriented to the transmission, distribution and internalization of a worldview to contribute to the consolidation of the necessary legitimacy to the (new) hegemonic project.